On projective Anosov subgroups of symplectic groups: research article - Pozzetti, Maria Beatrice; Tsouvalas, Konstantinos (Bulletin of the London Mathematical Society, 2023)
We prove that a word hyperbolic group whose Gromovboundary properly contains a 2-sphere cannot admita projective Anosov representation into 𝖲𝗉2𝑚(ℂ),𝑚∈ℕ. We also prove that a word hyperbolic group thatadmits a projective Anosov representation into 𝖲𝗉2𝑚(ℝ) is virtually a free group or virtually a surface group,a result established independently by Dey–Greenberg–Riestenberg.